Optimisation of power quality in solar/wind power stations using developed artificial bee/ant hybrid heuristic algorithm - Zile, Mehmet (Universitas Muhammadiyah Surakarta, 2021)
Voltage regulation needs to be optimised to reduce energy losses and improve power quality in renewable solar/wind plants. The Artificial Bee/Ant Hybrid Heuristic Algorithm has been developed in the study, and voltage regulation was optimised using this developed algorithm. A computer program in the C++ programming language was developed to prevent the undesired effects of electrical events occurring during the integration of renewable energy sources and to make the system work more efficiently. The interface of the program was made using the Visual Studio program. It became possible to produce power estimation, power quality estimation and power loss estimation using the intuitive artificial bee/ant hybrid algorithm created on the data set obtained from solar and wind power plants. It was found that there is a ± 4% difference between the values obtained with the developed algorithm and the computer program and the values obtained from the power plants. The developed algorithm and the computer program successfully optimise power quality in solar/wind power stations. The study makes it possible to estimate the amount of energy produced, the amount of energy loss, and the quality of energy in solar/wind power stations.